European study confirms the combination of fever and petechial rash as an important warning sign for childhood sepsis and meningitis. (21st March 2023) - Kohlmaier, Benno; Leitner, Manuel; Hagedoorn, Nienke N.; Borensztajn, Dorine M.; von Both, Ulrich; Carrol, Enitan D.; Emonts, Marieke; van der Flier, Michiel; de Groot, Ronald; Herberg, Jethro; Levin, Michael; Lim, Emma; et al.
Abstract: Aim: This study investigated febrile children with petechial rashes who presented to European emergency departments (EDs) and investigated the role that mechanical causes played in diagnoses. Methods: Consecutive patients with fever presenting to EDs in 11 European emergency departments in 2017–2018 were enrolled. The cause and focus of infection were identified and a detailed analysis was performed on children with petechial rashes. The results are presented as odds ratios (OR) with 95% confidence intervals (CI). Results: We found that 453/34010 (1.3%) febrile children had petechial rashes. The focus of the infection included sepsis (10/453, 2.2%) and meningitis (14/453, 3.1%). Children with a petechial rash were more likely than other febrile children to have sepsis or meningitis (OR 8.5, 95% CI 5.3–13.1) and bacterial infections (OR 1.4, 95% CI 1.0–1.8) as well as need for immediate life‐saving interventions (OR 6.6, 95% CI 4.4–9.5) and intensive care unit admissions (OR 6.5, 95% CI 3.0–12.5). Conclusion: The combination of fever and petechial rash is still an important warning sign for childhood sepsis and meningitis. Ruling out coughing and/or vomiting was insufficient to safely identify low‐risk patients.